2016
DOI: 10.1590/s1518-8787.2016050005965
|View full text |Cite
|
Sign up to set email alerts
|

Visceral leishmaniasis in the state of Sao Paulo, Brazil: spatial and space-time analysis

Abstract: OBJECTIVE To perform both space and space-time evaluations of visceral leishmaniasis in humans in the state of Sao Paulo, Brazil.METHODS The population considered in the study comprised autochthonous cases of visceral leishmaniasis and deaths resulting from it in Sao Paulo, between 1999 and 2013. The analysis considered the western region of the state as its studied area. Thematic maps were created to show visceral leishmaniasis dissemination in humans in the municipality. Spatial analysis tools Kernel and Ker… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
6

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 26 publications
3
22
0
6
Order By: Relevance
“…In this research, the peak activity of sand flies was found to be exactly 18-18.5 °C and the average humidity was 80-86 percent. Two studies for India and Brazil have found similar results with respect to the direct effects of temperature and humidity on leishmaniasis vectors development (28)(29)(30).…”
Section: Discussionmentioning
confidence: 73%
“…In this research, the peak activity of sand flies was found to be exactly 18-18.5 °C and the average humidity was 80-86 percent. Two studies for India and Brazil have found similar results with respect to the direct effects of temperature and humidity on leishmaniasis vectors development (28)(29)(30).…”
Section: Discussionmentioning
confidence: 73%
“…Os sistemas de informação geográfica têm sido amplamente empregados na avaliação da dispersão espacial e temporal da LV em vários estados brasileiros (ANTONIALLI et al, 2007;FURTADO et al, 2015;SILVA et al, 2017) e no exterior (ZHENG et al, 2018). Por meio deles, é possível identificar espacialmente padrões de distribuição, áreas de risco e prioritárias para que autoridades de saúde pública implementem e/ou otimizem as ações de controle e vigilância (CARDIM et al, 2016;KIRBY;DELMELLE;EBERTH, 2017). Diante do exposto, o presente estudo objetivou determinar o panorama espacial e demográfico atualizado da ocorrência de LV humana no estado de Mato Grosso entre 2001 e 2016, bem como verificar alterações nesse perfil ao longo do tempo.…”
Section: Referênciasunclassified
“…Temporal trend analyzes are widely used strategies for the surveillance and control actions focusing on vectorborne diseases such as dengue, yellow fever, malaria and leishmaniasis 10 . Another important surveillance tool is the Geographic Information System (GIS), used to analyze spatial patterns of diseases distribution, identifying risk areas, associated factors and indicating priority areas for the development of control actions 11 .…”
Section: Introdutionmentioning
confidence: 99%